THE FACTOR ANALYSIS WHICH AFFECTS STUDENT’S LEARNING ACHIEVEMENTS ON 4TH SEMESTER AT DIPLOMA III OF MIDWIFERY STUDY PROGRAM MATARAM HEALTH POLYTECHNIC - Ni Putu Dian Ayu Anggraeni; Ni Nengah Arini Murni (poltekkes kemenkes mataram, 2017)
Abstract : the students’ high or low achievement which is obtained by someone in learning is influenced by several factors, where the factors are connected each other from internal and external factors. According to the researcher, on second grade and fourth semesters where the students have adapted with teaching materials and academic system in the class or practice field. Therefore, the research objective was to know the factors that influence student’s learning achievements on fourth semester at Diploma III of Midwifery study Program, Mataram Health Polytechnic. This research was quantitative research and the method utilized was descriptive method. The population was 208 students at Diploma III of Midwifery Study Program in academic year 2014/2015 and the sample was purposive sampling technique based on inclusion and exclusion criterias that was the fourth semester student as many as 91 people. Data analysis in the study was descriptive statistical technique and analysis method was multiple linear regression analysis. The research finding was Fcount> Ftable (40.170> 3.96) with significant level 0.000 <0.05 which meant interest and learning motivation, the independence in learning, family environment, college environment, and academic counseling influenced the student’s learning achievement simultaneously on fourth semesters at Diploma III of Midwifery Study Program. The most dominant factor affected student’s achievement was the independence of learning with a significance value of 0.001. The determination result (R Square) of interest and motivation in learning, the independence of learning, family environment, college environment, and academic counseling had an effect 78.5% on learning achievement while the remaining 21.5% was influenced by other factors which were not investigated in the study. By providing opportunities for students to improve their motivation and their independence in learning through an ideal college environment and learning methods which more varieties and interesting thus the students are expected to develop their cognitive abilities hence thier learning achievement can improve properly.